Dapagliflozin for the treatment of heart failure with reduced ejection fraction in Brazil: a cost-effectiveness analysisResearch in context - Marcio Coutinho Xavier Naves; Angelica Amorim Amato; Ivan Ricardo Zimmermann; Henry Maia Peixoto (The Lancet Regional Health. Americas)
Summary: Background: Heart failure, a complex clinical syndrome with high morbidity and mortality, has become a significant burden on public health. Recently, a new class of antidiabetic agents–the sodium-glucose cotransporter 2 (SGLT2) inhibitors–was associated with a significant reduction on mortality and hospitalization in HF with reduced ejection fraction (HFrEF) when added to standard pharmacological treatment. Considering the lack of data on its cost-effectiveness, the present study aims to estimate the incremental cost-effectiveness ratio of add-on dapagliflozin treatment for HFrEF from the Brazilian public healthcare system perspective. Methods: We built a Markov model to estimate the clinical outcomes and costs of 1,000 hypothetical subjects with established HFrEF in a lifetime horizon. The model inputs were based on the Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure (DAPA-HF) trial and local data. The main outcome was the incremental cost-effectiveness ratio (ICER) per quality-adjusted life year (QALY) gained. Deterministic and probabilistic sensitivity analyses, as well as scenario analyses, were performed. Findings: The addition of dapagliflozin to standard care treatment in 1,000 HFrEF patients yielded an expected value of 366.99 additional QALYs at an incremental cost of US$ 1,517,878.49, resulting in an ICER of US$ 4,136.08 per QALY gained, being a cost-effective strategy considering the Brazilian official cost-effectiveness threshold (US$ 8,000/QALY). In probabilistic sensitivity analyses, 96.60% of the simulations were also cost-effective. In the scenario analyses, results were similar for individuals with and without diabetes. Interpretation: Dapagliflozin is likely to be cost-effective when added to standard HFrEF therapy in Brazil. Funding: This study was supported by the National Institute of Science and Technology for Health Technology Assessment (Instituto de Avaliação de Tecnologias em Saúde—IATS).